2021
DOI: 10.1186/s12989-021-00418-x
|View full text |Cite
|
Sign up to set email alerts
|

Repeated oral administration of low doses of silver in mice: tissue distribution and effects on central nervous system

Abstract: Background Widespread use of silver in its different forms raises concerns about potential adverse effects after ingestion, the main exposure route for humans. The aim of this study was to investigate in CD-1 (ICR) male mice the tissue distribution and in vivo effects of 4-week oral exposure to 0.25 and 1 mg Ag/kg bw 10 nm citrate coated silver nanoparticles (AgNPs) and 1 mg Ag/kg bw silver acetate (AgAc) at the end of treatment (EoT) and after 4 weeks of recovery. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 65 publications
0
18
0
Order By: Relevance
“…This extensive usage of AgNPs and their proven ability to cross biological barriers, such as the blood-brain barrier, have raised concerns about their potential influence on brain functions. Results obtained by Recordati et al showed high deposition of silver in the brain after oral exposure of environmentally relevant dose of citrate-coated AgNPs at the end of the administration as well as after 4 weeks of recovery that highlighted slow elimination of Ag from the brain structures [23]. Our previous study has also shown that oral administration of AgNPs at a relatively small concentration resulted in a time-dependent accumulation of silver in the brain, particularly in the hippocampus, and simultaneous deterioration of learning skills in rats [16,24].…”
Section: Discussionmentioning
confidence: 96%
“…This extensive usage of AgNPs and their proven ability to cross biological barriers, such as the blood-brain barrier, have raised concerns about their potential influence on brain functions. Results obtained by Recordati et al showed high deposition of silver in the brain after oral exposure of environmentally relevant dose of citrate-coated AgNPs at the end of the administration as well as after 4 weeks of recovery that highlighted slow elimination of Ag from the brain structures [23]. Our previous study has also shown that oral administration of AgNPs at a relatively small concentration resulted in a time-dependent accumulation of silver in the brain, particularly in the hippocampus, and simultaneous deterioration of learning skills in rats [16,24].…”
Section: Discussionmentioning
confidence: 96%
“… 44–46 Recordati et al observed slow clearance of silver and ultrastructural changes of the blood-brain barrier after oral administration of 1 mg/kg AgNPs and silver acetate in mice, without any treatment-related signs or effects on body and organ weights. 47 …”
Section: Characteristics and Performance Of Agbmsmentioning
confidence: 99%
“…The amount of silver that remained in the brain was approximately equal for both types of nanoparticles. Other authors have also established the persistence of silver accumulated in the brain even after a period of clearance, highlighting its slow elimination from this organ [31].…”
Section: Discussionmentioning
confidence: 93%